Localization of the binding site of the C-terminal domain of cardiac myosin-binding protein-C on the myosin rod. - Flashman, E; Watkins, H; Redwood, C (2007)
cMyBP-C [cardiac (MyBP-C) myosin-binding protein-C)] is a sarcomeric protein involved both in thick filament structure and in the regulation of contractility. It is composed of eight IgI-like and three fibronectin-3-like domains (termed C0-C10). Mutations in the gene encoding cMyBP-C are a principal cause of HCM (hypertrophic cardiomyopathy). cMyBP-C binds to the LMM (light meromyosin) portion of the myosin rod via its C-terminal domain, C10. We investigated this interaction in detail to determine whether HCM mutations in beta myosin heavy chain located within the LMM portion alter the binding of cMyBP-C, and to define the precise region of LMM that binds C10 to aid in developing models of the arrangement of MyBP-C on the thick filament. In co-sedimentation experiments recombinant C10 bound full-length LMM with a K(d) of 3.52 microM and at a stoichiometry of 1.14 C10 per LMM. C10 was also shown to bind with similar affinity to LMM containing either the HCM mutations A1379T or S1776G, suggesting that these HCM mutations do not perturb C10 binding. Using a range of N-terminally truncated LMM fragments, the cMyBP-C-binding site on LMM was shown to lie between residues 1554 and 1581. Since it had been reported previously that acidic residues on myosin mediate the C10 interaction, three clusters of acidic amino acids (Glu1554/Glu1555, Glu1571/Glu1573 and Glu1578/Asp1580/Glu1581/Glu1582) were mutated in full-length LMM and the proteins tested for C10 binding. No effect of these mutations on C10 binding was however detected. We interpret our results with respect to the localization of the proposed trimeric collar on the thick filament.